Knowledge of cervical cancer and barriers to screening among women in a city in Northern Nigeria (2021)
Aim This study assessed the knowledge of cervical cancer and barriers to cervical screening uptake among women of reproductive age in a city in Northern Nigeria to guide the development of interventions. Subject and Methods This was a cross-sectional study with women aged 15 to 49 years. A multi-stage sampling technique was used to select 230 women in Gombe state, Nigeria. A semi-structured, interviewer-administered questionnaire was used for data collection and analysed using descriptive and inferential statistics at 0.05 level of significance. Results The respondents’ age was 29.6 ± 8.06 years and 52.2% were Muslims. Over one third (34.3%) have tertiary-level education. Few (4.8%) had good knowledge of cancer of the cervix. Only 9.5% of the respondents aged 25-49 years had undergone cervical cancer screening using pap smear test; the majority (90.5%) did not have access to cervical cancer screening services in their communities. Barriers to cervical cancer screening uptake were: low perception of risk (32.8%), screening not recommended by a health worker (32.8%), poor awareness (32.2%) and lack of of clinics for cervical cancer screening in their communities (31.5%). There was an association between respondents’ attitude, educational level, income, religion, availability of cervical cancer screening services in communities, and the uptake of cervical cancer screening (p < 0.05). Conclusion This study provides information on the barriers to cervical screening uptake by women of reproductive age in northern Nigeria. These highlight the need for multi-component, multi-level interventions in Northern Nigeria to improve knowledge on the benefits of cervical screening. Targeted interventions on the identified barriers are the key steps to eliminatethe challenges to cervical screening utilisation.